Dynamic stress–strain response of graphene nanocomposites. (November 2020) - Sadeghpour, Ebrahim; Guo, Yangbo; Chua, Daniel; Shim, Victor P.W.
Highlights: Investigation into uniaxial tensile response of a PVA-graphene oxide nanocomposite over a strain rate range of 0.003–1200/s. Identification and analysis of interfacial slip between polymer matrix and filler as a dominant mechanism influencing the stress–strain response. Simulation of the mechanical response of the nanocomposite using a modified Mori-Tanaka approach which accommodates the effect of interfacial slip. Analysis of the rate sensitivity of the nanocomposite by examination of the initial elastic stiffness and stress level at a strain of 0.1, as a function of strain rate. Abstract: The dynamic stress–strain response of a polyvinyl alcohol (PVA) – graphene oxide (GO) nanocomposite is examined through tensile testing over a strain rate range of 0.003–1200/s, as well as via theoretical microscale modeling. PVA-GO samples with various GO content were prepared and subjected to uniaxial tension using a universal testing machine and a split Hopkinson tension bar arrangement. In previous studies by the authors [1, 2], interfacial slip between the GO flakes and PVA matrix was identified as a key mechanism in the mechanical behavior of the nanocomposite, and a modified Mori-Tanaka (M-T) approach was developed to accommodate the effect of slip. The modified M-T method was employed to model the stress–strain response of the PVA-GO nanocomposite at various strain rates, and close agreement between the theoretical and experimental results was observed. The rate sensitivity of PVA and its nanocomposites was analyzed by determining the initial elastic stiffness of specimens and their stress corresponding to a strain of 0.1, as functions of logarithmic strain rate ( log ( ε ˙ ) ); it was found that both these parameters increase linearly with log ( ε ˙ ) . Moreover, the rate of increase in initial elastic stiffness with log ( ε ˙ ) increases with GO content. In terms of the relationship between the stress at a strain of 0.1 and the logarithmic strain rate ( log ε ˙ ), both PVA and its nanocomposites display curves with similar profiles.